Evaluation of E-Bupot Unification System Based on Taxpayer Perspective - Mavira Nabila Putri; Siti Nuryanah (Jurnal Riset Perpajakan: Amnesty, 2023)
State revenue from taxes can be said to be the largest source of income for Indonesia. Therefore, in order to achieve the increasing tax revenue target, the government made updates to the tax system, namely E-Bupot Unifikasi. The evaluation was conducted to analyze whether the existing development makes it easier for taxpayers to report their taxes and whether the e-Bupot Unification system is more efficient and effective than e-Bupot 23/26. The evaluation is based on the TAM (Technology Acceptance Model) and DSS (DeLone and McLean IS Success Model) models. In this study, the object of research was conducted on taxpayers (clients of PT OCT and PT OCT). The results of evaluating the effectiveness of the e-Bupot Unification system as measured by the TAM and DSS models based on the perceptions of PT OCT clients show that the e-Bupot Unification system as a whole is effective. This is based on the ability of the Unification e-Bupot system to assist users in reporting their taxes. Meanwhile, from the perception of PT OCT is Bukti Potong Unifikasi as a result of the e-Bupot Unifikasi system received from each client as a whole has not shown an increase in its effectiveness to credit PT OCT tax from the previous e-Bupot system. The implication of this research is that improvements to the e-Bupot Unification system can be made and by considering other types of taxes such as Income Tax 21 to be reported in the e-Bupot Unification system so that in the future it can make it easier for taxpayers to report their taxes. Taxpayers who are deducted are expected to report according to the invoice period issued by the opposite transaction, provide notifications every month periodically so that customers provide Proof of Deduction in the same period as the invoice, make manual calculations of Income Tax, include clear, complete, and updated information.